Approaches to advance scientific understanding of macrosystems ecology. Issue 1 (1st February 2014) - Levy, Ofir; Ball, Becky A; Bond-Lamberty, Ben; Cheruvelil, Kendra S; Finley, Andrew O; Lottig, Noah R; Punyasena, Surangi W; Xiao, Jingfeng; Zhou, Jizhong; Buckley, Lauren B; Filstrup, Christopher T; Keitt, Tim H; et al.
Abstract : The emergence of macrosystems ecology (MSE), which focuses on regional‐ to continental‐scale ecological patterns and processes, builds upon a history of long‐term and broad‐scale studies in ecology. Scientists face the difficulty of integrating the many elements that make up macrosystems, which consist of hierarchical processes at interacting spatial and temporal scales. Researchers must also identify the most relevant scales and variables to be considered, the required data resources, and the appropriate study design to provide the proper inferences. The large volumes of multi‐thematic data often associated with macrosystem studies typically require validation, standardization, and assimilation. Finally, analytical approaches need to describe how cross‐scale and hierarchical dynamics and interactions relate to macroscale phenomena. Here, we elaborate on some key methodological challenges of MSE research and discuss existing and novel approaches to meet them.